Coverage of the 2016-2017 Economic Recession in Selected Newspapers in Nigeria (Global Journal of Human-Social Science, 2020)
The mass media play a critical role in raising and creating awareness on issues that affect society. One such subject that the media must bring to the attention of all-government and individuals in the community is an economic recession. The continuous instability of the Naira against the dollar, geometrical increase in unemployment, the rising cost of living, non-payment of salaries to the employed, the unpredictable prices of crude oil among other things were issues the common man in Nigeria faced as a result of economic recession. How such stories was reported in the media is a critical subject for empirical inquiry, hence the need for this study. The paramount objective of this study was to analyze the newspaper coverage of the 2016-2017 economic recession in Nigeria. The newspapers selected for the study include Daily Sun, The Guardian, and Vanguard. The coverage examined frequency, story genre, story prominence, story direction, story depth. Agenda setting and priming theory served as the theoretical foundation of the study. The study employed content analysis as research design. The Code sheet was the instrument used to gather data. Results of the study showed that the frequency of coverage on economic recession stories is 243 in the print media; prominence attached to economic recession stories is low, and the dominant story genre is news.
Keywords: economic recession; newspapers; coverage; nigeria